Thymic Hyperplasia after Lung Transplantation Imitating Posttransplant Lymphoproliferative Disorder - Christina Maria Steger; Severin Semsroth; Thomas Hager; Ralf Rieker; Ludwig Müller (Case Reports in Transplantation)
Thymic hyperplasia is usually associated with the treatment of malignant tumours and is sometimes linked with endocrine diseases. For the first time, we report a case of thymic hyperplasia in a patient 2 years after bilateral lung transplantation. Contrast-enhanced chest CT scan was highly suspicious for a posttransplant lymphoma or thymoma. Therefore, the patient received total thymectomy. Excised specimens were sent to the Department of Pathology. Unexpectedly, the histological examination revealed hyperplastic thymic tissue without evidence for a posttransplant lymphoproliferative disorder or malignancy.